Effect of different host plants on growth and development of epilachna beetle (Bangladesh Journal of Agricultural Research, 2009)
An experiment was conducted to study the effect of four different host plants viz., teasel gourd, bitter gourd, sponge gourd, and yard long bean on the growth and development of Epilachna dodecastigma Wied under laboratory condition. The number of eggs laid by female beetle was significantly highest feeding on teasel gourd leaves and lowest on yardlong bean leaves. Egg hatching was faster on yardlong bean and delayed on bitter gourd. The host plant, such as sponge gourd produced the large sized larvae, while large pupa and adult were developed by feeding teasel leaves. The smallest larvae, pupae, and adults were found on the consumption of yardlong bean leaves. Highest larval duration was found on sponge gourd followed by bitter gourd and yardlong bean. Both larval and adult food consumption was highest on teasel gourd and lowest on yardlong bean. Considering the biological characteristics and leaf consumption, the plant teasel gourd appeared to be the best host plant for E. dodecastigma. Key Words: Host plant, growth and development, Epilachna dodecastigma, leaf consumption. DOI: 10.3329/bjar.v34i3.3965 Bangladesh J. Agril. Res. 34(3) : 403-410, September 2009